Special issue: NBS for resilient cities and communities the circular economy of water – investigating the spatial variation of rainwater harvesting systems in Ireland - Liam McCarton; Sean O'Hogain; Ahmed Nasr (Nature-Based Solutions, 2022)
Rainwater harvesting is a nature based solution which has the potential to replace non-potable use for toilet flushing. It's integration into a national supply strategy in Ireland has been limited by uncertainty over its reliability as a supply option. This study sets out to address some of these uncertainties by investigating the spatial variation of rainwater harvesting systems in Ireland. Daily non-potable water use was monitored in a set of four study households (A,B,C,D) over 24-months. A standardised methodology to predict the hydraulic efficiency of rainwater harvesting for any location was developed from this dataset and applied to develop national supply charts. The average daily non-potable demand for toilet flushing (DN,d) in the study households ranged from 27.89 L/day to 473.37 L/day, equivalent to a per capita consumption range of 13.9 L/hd/dayay to 94.67 L/hd/dayay. The higher demand was due to a leaking toilet cistern in one of the houses and shows the potential impact on daily household water use. The results showed that house A and house C could potentially meet 100% of toilet demand from a rainwater harvesting system with minimum storage requirements. Within these houses a rainwater harvesting system could potentially reduce annual mains water consumption by 25% and 22% respectively. House B and D will not generate sufficient excess to balance supply and demand so will always operate at a hydraulic efficiency of less than 100%. Within these households, a rainwater harvesting system has the potential to reduce public mains water consumption by 18% and 12% respectively. The hydraulic efficiency methodology was then applied to investigate rainwater harvesting in a “Standard House” with a roof catchment area of 75m2 for 2, 3 and 4 person-households based on an analysis of 30 year daily rainfall records across 26 catchments. A set of design charts for Ireland is published in this paper. This study has developed a rapid methodology which has the potential to be used in any location once the supply and demand profiles can be accurately estimated.